2005
DOI: 10.1099/mic.0.27865-0
|View full text |Cite
|
Sign up to set email alerts
|

Bap-dependent biofilm formation by pathogenic species of Staphylococcus: evidence of horizontal gene transfer?

Abstract: The biofilm-associated protein (Bap) is a surface protein implicated in biofilm formation by Staphylococcus aureus isolated from chronic mastitis infections. The bap gene is carried in a putative composite transposon inserted in SaPIbov2, a mobile staphylococcal pathogenicity island. In this study, bap orthologue genes from several staphylococcal species, including Staphylococcus epidermidis, Staphylococcus chromogenes, Staphylococcus xylosus, Staphylococcus simulans and Staphylococcus hyicus, were identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
221
3
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(242 citation statements)
references
References 44 publications
8
221
3
10
Order By: Relevance
“…Surprisingly, the #2056 showed strong biofilm formation and it is thus reasonable to consider it has a major variation in the ica operon or it has a different locus which plays an important role in biofilm development. Recent studies have shown a PIA-independent mechanism mediating biofilm formation in clinical isolates of S. epidermidis and S. aureus [14,28] and a biofilm-associated protein (Bap) being involved in strains isolated from chronic mastitis cases [29] and S. aureus [30]. Similarly, Simojoki et al [3] found that primers used for detecting bap and other biofilm-associated genes do not identify all CNS capable of biofilm production.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the #2056 showed strong biofilm formation and it is thus reasonable to consider it has a major variation in the ica operon or it has a different locus which plays an important role in biofilm development. Recent studies have shown a PIA-independent mechanism mediating biofilm formation in clinical isolates of S. epidermidis and S. aureus [14,28] and a biofilm-associated protein (Bap) being involved in strains isolated from chronic mastitis cases [29] and S. aureus [30]. Similarly, Simojoki et al [3] found that primers used for detecting bap and other biofilm-associated genes do not identify all CNS capable of biofilm production.…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that biofilms are the basis for persistent or chronic bacterial infections . The implication of biofilms in chronic infections has triggered an increasing interest in the organization of genes involved in biofilm formation (Caizza and O'Toole, 2005;Tormo et al, 2005). The icaADBC cluster, an operon present in S. aureus and S. epidermidis, participates in biofilm formation by encoding proteins involved in the synthesis of a biofilm matrix polysaccharide (Cucarella et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The lower detection of icaA, and therefore the differences in the prevalence rates can be attributed to the variation in DNA sequences. This may lead to failed amplification of the genes in some isolates and consequently false negative results (Tormo et al, 2005;Ferrer et al, 2012;Darwish and Asfour, 2013). Since ica locus is responsible for the production of intracellular adhesion polysaccharide (PIA) (Krewer et al, 2015) and thus forming the multiple layer of cell in a slime matrix characteristic of the staphylococcal biofilm (Darwish and Asfour, 2013), the presence of icaA or icaD negative strain, with biofilm production in Congo Red Agar and microplate assay isolates, can be accounted for by an ica gene independent control of slime production/adhesion mechanism (Liberto et al, 2009).…”
Section: Phenotypic and Genotypic Biofilm Productionmentioning
confidence: 99%